Whole Blood Measurement of Histone Modifications Linked to the Epigenetic Regulation of Gene Expression. Issue 1 (5th January 2015) - Watson, Maria; Hedley, David
Abstract: Rapid progress is being made to understand the regulatory mechanisms that underlie the epigenetic control of gene expression through histone modification. It is now recognized that this plays a major role in normal development and disease. This unit describes the application of flow cytometry to the study of epigenetic mechanisms by combining labeling of individual histone modifications and phenotypic markers, and it also discusses practical issues to optimize staining. The focus is on normal blood and samples from leukemia patients, but it can also be applied to cells grown in tissue culture. © 2015 by John Wiley & Sons, Inc.